2012
DOI: 10.1136/postgradmedj-2011-130083
|View full text |Cite
|
Sign up to set email alerts
|

Poor professionalism identified through investigation of unsolicited healthcare complaints

Abstract: The vast majority of unprofessional behaviour identified related to non-cognitive, professionalism aspects of care. Complaints pertaining to unsatisfactory communication were especially noticeable. Incongruence is noted between the physicians' and the patients' perception of actual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…The rich, unstructured narrative within complaints complicates reliable and meaningful extraction of quality and safety insights 16. Various coding taxonomies have been developed to support complaints teams and researchers in codifying complaints reliably 7 9 11 55 65 68–78. To achieve reliable aggregated analysis, the taxonomy should fulfil the following minimum criteria: the categories in the framework are collectively exhaustive, mutually exclusive and reflect patient voice as reported in complaints (ie, validity) 11 79 80.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rich, unstructured narrative within complaints complicates reliable and meaningful extraction of quality and safety insights 16. Various coding taxonomies have been developed to support complaints teams and researchers in codifying complaints reliably 7 9 11 55 65 68–78. To achieve reliable aggregated analysis, the taxonomy should fulfil the following minimum criteria: the categories in the framework are collectively exhaustive, mutually exclusive and reflect patient voice as reported in complaints (ie, validity) 11 79 80.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative complaints analysis studies highlight the need for additional qualitative analysis to derive granular and actionable learning lessons 7 69 81. A two-step ‘spotlight’ approach has been suggested that combines quantitative trend analysis with targeted qualitative analysis 10.…”
Section: Resultsmentioning
confidence: 99%
“…It is long practice time that makes them accumulate work experience, such as communication skills. [ 1315 ] Then, a more persuasive and convinced physician will have closer follow-up of patients and even better treatment outcomes. In turn, patients marked higher scores on the physicians accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the self-assessment of Respect for others, Altruism/Humanitarian and Honor/Integrity turn to be lower. Van Mook [15] from a Holland teaching hospital investigated 140 complaints in 5 years and found that the complaints focus more on medical professionalism instead of medical errors. The external influence factor has a mutual effect between the patients’ complaints and medical professionalism, which need the public's attention.…”
Section: Discussionmentioning
confidence: 99%
“…Complaints can be a window into unprofessional behavior, or into gaps between physician behavior and patients’ expectations, and can be predictive of malpractice risk [13]. The workshop explored whether patient complaints are surrogate measures of a lack of professionalism and whether they can be used as tools to enhance it .…”
Section: Synopsismentioning
confidence: 99%